Identification of two partners from the bacterial Kef exchanger family for the apical plasma membrane V-ATPase of Metazoa. - Day, J.P.; Wan, S.; Allan, A.K.; Kean, L.; Davies, S.A.; Gray, J.V.; Dow, J.A.T. (Journal of Cell Science, 2008)
The vital task of vectorial solute transport is often energised by a plasma membrane, proton-motive V-ATPase. However, its proposed partner, an apical alkali-metal/proton exchanger, has remained elusive. Here, both FlyAtlas microarray data and in situ analyses demonstrate that the bacterial kefB and kefC (members of the CPA2 family) homologues in Drosophila, CG10806 and CG31052, respectively, are both co-expressed with V-ATPase genes in transporting epithelia. Immunocytochemistry localises endogenous CG10806 and CG31052 to the apical plasma membrane of the Malpighian (renal) tubule. YFP-tagged CG10806 and CG31052 both localise to the plasma membrane of Drosophila S2 cells, and when driven in principal cells of the Malpighian tubule, they localise specifically to the apical plasma membrane. V-ATPase-energised fluid secretion is affected by overexpression of CG10806, but not CG31052; in the former case, overexpression causes higher basal rates, but lower stimulated rates, of fluid secretion compared with parental controls. Overexpression also impacts levels of secreted Na+ and K+. Both genes rescue exchanger-deficient (nha1 nhx1) yeast, but act differently; CG10806 is driven predominantly to the plasma membrane and confers protection against excess K+, whereas CG31052 is expressed predominantly on the vacuolar membrane and protects against excess Na+. Thus, both CG10806 and CG31052 are functionally members of the CPA2 gene family, colocalise to the same apical membrane as the plasma membrane V-ATPase and show distinct ion specificities, as expected for the Wieczorek exchanger.